Some of the problems of development of legislation in the field of land law relations in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
In the Republic of Kazakhstan sources of land law is the Constitution of the Republic of Kazakhstan, theLand Code of the Republic of Kazakhstan and other regulatory legal acts. Adopted in July 20, 2003 LandCode of the Republic of Kazakhstan – introduced private ownership of agricultural land. Land reform isthe linchpin of economic transformation, and its direction is determined relationship to the land. And at thepresent stage of development of land relations pravovvyh require regulation of such issues as promotingimproved quality of land, penalties for environmental damage from fines to termination of the land userights, the introduction of compensatory payments, compensation for damages and losses in the seizure ofland, the formation of the land market, strengthening responsibility for the violation of land legislation. Landreform is a combination of legal, economic, organizational and technical measures ensuring a qualitativelynew structure of land ownership and land use in the period since the republic's economy into the marketeconomy.Keywords: land relations, private property, public property, the bill, land laws.